Training Intensity Distribution and Changes in Performance and Physiology of a 2nd Place Finisher Team of the Race across America Over a 6 Month Preparation Period - Manunzio, Christian; Mester, Joachim; Kaiser, Walter; Wahl, Patrick (Frontiers in Physiology, 2016)
Aim To monitor the training intensity distribution (TID) and the development of physiological and performance parameters. Methods During their preparation period for the RAAM, 4 athletes (plus 1 additional backup racer) performed 3 testing sessions; one before, one after 3 and one after 6 months of training. VO2max, maximal rate of lactate accumulation (dLa/dtmax), critical power, power output at lactate minimum (MLSSP), peak and mean power output during a sprint test, heart rate recovery, isometric strength, jumping height, and body composition were determined. All training sessions were recorded with a power meter. The endurance TID was analyzed based on the time in zone approach, according to a classical 3-zone model, including all power data of training sessions, and a power specific 3-zone model, where time with power output below 50% of MLSSP was not considered. Results The TID using the classical 3-zone model reflected a pyramidal TID (zone 1: 63 ± 16%, zone 2: 28 ± 13% and zone 3: 9 ± 4%). The power specific 3-zone model resulted in a threshold-based TID (zone 1: 48 ± 13%, zone 2: 39 ± 10%, zone 3: 13 ± 4%). VO2max increased by 7.1 ± 5.3% (P = 0.06). dLa/dtmax decreased by 16.3 ± 8.1% (P = 0.03). Power output at lactate minimum and critical power increased by 10.3 ± 4.1% and 16.8 ± 6.2% (P = 0.01), respectively. No changes were found for strength parameters and jumps. Conclusion The present study underlines that a threshold oriented TID results in only moderate increases in physiological parameters. The amount of training below 50% of lactate threshold ( 28% of total training time) is remarkably high. Researchers, trainers, and athletes should pay attention to the different ways of interpreting training power data, to gain realistic insights into the TID and the corresponding improvements in performance and physiological parameters. Keywords endurance performance, training intensity distribution, critical power, VO2max, maximal rate of lactate accumulation.